2022
DOI: 10.3390/buildings12070910
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Workplace Well-Being: Building Construction Projects

Abstract: This study explores the factors affecting workplace well-being in building construction projects. The objectives of this study are (1) to investigate the critical factors for workplace well-being in building construction projects, (2) to compare the critical factors between large enterprises (LEs) and small-medium enterprises (SMEs), and (3) to compare the critical factors between high-rise building construction projects and non-high-rise building construction projects. Data from 21 semi-structured interviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 69 publications
(54 reference statements)
1
18
0
1
Order By: Relevance
“…A research that investigated the association between safety and quality using information and communication technology discovered that this technology might lead to a 90% reduction in risky behaviors (Shohet et al 2019). Maintaining high levels of safety through communication can have synergistic benefits among workers (Rani et al 2022). Communication between management and workers on safety is critical for improving safety performance (Alsamadani et al 2013;Chan et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A research that investigated the association between safety and quality using information and communication technology discovered that this technology might lead to a 90% reduction in risky behaviors (Shohet et al 2019). Maintaining high levels of safety through communication can have synergistic benefits among workers (Rani et al 2022). Communication between management and workers on safety is critical for improving safety performance (Alsamadani et al 2013;Chan et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to the Indian construction industry, depending on the role, levels of stress vary. Physiological, physiological, and sociological factors significantly affect professionals in India [30][31][32]. If the employee is satisfied with the quality of worklife (QWL), they may balance their personal and professional life, leading to a healthy WLB.…”
Section: Impact Of the Work-family Interface (Wfi)mentioning
confidence: 99%
“…To address workplace well-being issues in the construction industry, researchers have started to explore the topic. For instance, Rani et al [14] have identified the critical factors influencing workplace well-being in construction projects [14]. Also, Mostert et al [15] have identified the negative impact of burnout on workplace well-being in the construction industry.…”
Section: Literature Review 21 Workplace Well-being In the Constructio...mentioning
confidence: 99%
“…[23] PH09 Workload [14], [24], [25], [26], [27] PH17 Transportation facilities for construction workers [14], [28] Psychological factors…”
Section: Constructs Code Factors Affecting Workplace Well-being Refer...mentioning
confidence: 99%